In memoriam Yevgen Pysanets (1949–2016) - Maliuk, A.Yu. (Збірник праць Зоологічного музею, 2017)
Irretrievable loss incurred the biological science, museology and education in Ukraine. On 15 October 2016, at age 67, suddenly died the famous zoologist, teacher, museum activist, founder and first president of the Ukrainian Herpetological Society, head of the Zoological Department at the National Museum of Natural History, NAS of Ukraine, doctor of biological sciences, professor Yevgen Maksymovych Pysanets. Since 1999, he had been leading of the Zoological Department for seventeen years.